PERAN GURU DALAM “PRESENTASI SISWA” SMP N 3 JOMBANG KELAS IX B - Resdianto Permata Raharjo; Haris Supratno; Yulianah Prihatin (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
Education is mandatory for the nation's children, without education the whole community does not have the competence to lead or teach something. Schools are places where the learning process takes place, where teachers act as teachers and educators become students as learners. The learning process cannot be separated from the components that support it. One of the components is learning evaluation. Evaluation is obtained intentionally to get the desired data that can be used as a decision. Evaluation activities are carried out systematically, and structurally require a lot of data or information and are clear. For example, if the teacher wants to measure the students' ability to accept the material given, the teacher deliberately asks questions to determine the level of students' understanding. In addition, by asking questions, teachers can evaluate students in the learning process through various kinds. Learning by observing students is a way to improve the quality of learning so that the data obtained from these activities will be used so that teachers can make the right decisions. This development is also accompanied by changes in student conditions from year to year. Evaluation of learning also develops as the field conditions.